2013
DOI: 10.1128/aem.01445-13
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Malic Acid Production in Aspergillus oryzae under Nitrogen Starvation Conditions

Abstract: bMalic acid has great potential for replacing petrochemical building blocks in the future. For this application, high yields, rates, and titers are essential in order to sustain a viable biotechnological production process. Natural high-capacity malic acid producers like the malic acid producer Aspergillus flavus have so far been disqualified because of special growth requirements or the production of mycotoxins. As A. oryzae is a very close relative or even an ecotype of A. flavus, it is likely that its high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 29 publications
1
48
4
Order By: Relevance
“…Recently, a study in Aspergillus oryzae revealed that nitrogen starvation promotes intracellular malic acid biosynthesis (34). With its large expansion of low-pH secretory hydrolytic enzymes (35), A. oryzae is becoming a promising species for the industrial production of malic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in Aspergillus oryzae revealed that nitrogen starvation promotes intracellular malic acid biosynthesis (34). With its large expansion of low-pH secretory hydrolytic enzymes (35), A. oryzae is becoming a promising species for the industrial production of malic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the muC strain was grown in the low oxygen tension condition, which made TCA cycle very weak. Thus, the malic acid production should use the pathway (1), which involved PEP carboxykinase converting PEP to oxaloacetate and malate dehydrogenase converting oxaloacetate to malate and this pathway was found in another aerobe: Aspergillus oryzae , which was a malate producer . The native anaplerotic reaction such as the reaction converting pyruvate to oxaloacetate by pyruvate carboxylase was found in T. fusca .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the malic acid production should use the pathway (1), which involved PEP carboxykinase converting PEP to oxaloacetate and malate dehydrogenase converting oxaloacetate to malate and this pathway was found in another aerobe: Aspergillus oryzae, which was a malate producer. 16 The native anaplerotic reaction such as the reaction converting pyruvate to oxaloacetate by pyruvate carboxylase was found in T. fusca. There is another route converting the malate to pyruvate or pyruvate to malate, catalyzed by malate dehydrogenase (oxaloacetate-decarboxylating).…”
Section: Pathways To Malic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this microbe produces aflatoxin, which makes it unsuitable for use in food-grade chemical production. Other species of Aspergillus, such as Aspergillus niger ATCC10577 (West, 2011), Aspergillus oryzae NRRL3488 (Knuf et al, 2013), and Aspergillus oryzae DSM 1863 (Knuf et al, 2014), are found to produce 17, 30.2, and 42 g/L L-malate, respectively. In addition, the isolated microorganisms such as Schizophyllum commune and Zygosaccharomyces rouxii are found to accumulate 18 and 75 g/L L-malate, respectively, but the yield and productivity are low, limiting their usefulness for industrial production (Kawagoe et al, 1997;Taing and Taing, 2007).…”
Section: Introductionmentioning
confidence: 99%